SARS-CoV-2 Specific IgG Antibodies Persist Over a 12-Month Period in Oral Mucosal Fluid Collected From Previously Infected Individuals - Chellamuthu, Prithivi; Angel, Aaron N.; MacMullan, Melanie A.; Denny, Nicholas; Mades, Aubree; Santacruz, Marilisa; Lopez, Ronell; Bagos, Cedie; Casian, Joseph G.; Trettner, Kylie; Lopez, Lauren; Nirema, Nina; et al. (Frontiers in Immunology, 2021)
Background Developing an understanding of the antibody response, seroprevalence, and seroconversion from natural infection and vaccination against SARS-CoV-2 will give way to a critical epidemiological tool to predict reinfection rates, identify vulnerable communities, and manage future viral outbreaks. To monitor the antibody response on a larger scale, we need an inexpensive, less invasive, and high throughput method. Methods Here we investigate the use of oral mucosal fluids from individuals recovered from SARS-CoV-2 infection to monitor antibody response and persistence over a 12-month period. For this cohort study, enzyme-linked immunosorbent assays (ELISAs) were used to quantify anti-Spike(S) protein IgG antibodies in participants who had prior SARS-CoV-2 infection and regularly (every 2-4 weeks) provided both serum and oral fluid mucosal fluid samples for longitudinal antibody titer analysis. Results In our study cohort (n=42) with 17 males and 25 females with an average age of 45.6 +/- 19.3 years, we observed no significant change in oral mucosal fluid IgG levels across the time course of antibody monitoring. In oral mucosal fluids, all the participants who initially had detectable antibodies continued to have detectable antibodies throughout the study. Conclusions Based on the results presented here, we have shown that oral mucosal fluid-based assays are an effective, less invasive tool for monitoring seroprevalence and seroconversion, which offers an alternative to serum-based assays for understanding the protective ability conferred by the adaptive immune response from viral infection and vaccination against future reinfections.